Faktor-faktor yang Mempengaruhi Produksi Karet di Kecamatan Namohalu Esiwa Kabupaten Nias Utara - GEA, RESTY; ANTARA, MADE; DEWI, NI LUH PRIMA KEMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Factors That Influence Rubber Production in Namohalu District Esiwa North Nias District. Rubber has good prospects for farmers' livelihoods. Production and productivity of rubber plants do not always increase, sometimes there is a decrease. This research is intended to identify the factors that influence rubber production in Namohalu Esiwa District, North Nias Regency. This research was conducted from September to December 2020. The research respondents were 91 people. The method of analysis used multiple linear regression test, autocorrelation test, classical assumption test, hypothesis testing, and descriptive analysis. The characteristics of rubber farmers show that the percentage of high school education is 32%, the age of the farmer is 51%, and the experience of farming is 32%. The influencing factors include plant age (X1), labor (X4), land area (X6), fertilizer use (X7), which have a significant effect on rubber production. The variables of land ownership (X2), type of plant (X3), number of tapping days (X5) did not have a significant effect on rubber production in Namohalu Esiwa District, North Nias Regency. Cultivation constraints experienced by rubber farmers include technical constraints, economic constraints, and social constraints. Suggestions that can be recommended are expected for rubber farmers to continue to increase rubber production and increase knowledge and skills in rubber farming. What farmers need from the government is to provide assistance programs and capital. For further researchers, they can examine variables that were not found in this study.